The Second World War in Polish Cinema. Recent Filmic Approaches and the Reception in Poland and Germany - Hiemer, Elisa-Maria (Poznańskie Studia Slawistyczne, 2017)
The article deals with the representations of history in contemporary Polish cinema. On the occasion of the 70th anniversary of the Warsaw Uprising, Jan Komasa released two fundamentally different films within one year. By an analysis focusing the context, the artistic product and the reception, the author intends to decode the different messages and reception offers. The intended reception is then contrasted to the real reception referring to the reactions in Polish and (in the case of Miasto 44) in German media.